THU0174 ANTI-IL-6 RECEPTOR ANTIBODY AMELIORATES DISEASE ACTIVITY OF RHEUMATOID ARTHRITIS PATIENTS WITH KNEE JOINT INVOLVEMENT -ANSWER COHORT STUDY-. (2nd June 2020) - Maeda, Y.; Hirano, T.; Hara, R.; Ebina, K.; Hashimoto, M.; Yamamoto, W.; Murakami, K.; Kotani, T.; Hata, K.; Son, Y.; Amuro, H.; Onishi, A.; et al.
Abstract : Background: It has been reported that rheumatoid arthritis (RA) patients who have large joint involvement associated with higher serological inflammatory markers and more functional disability 1 . Moreover, a previous report showed that these patients were more difficult to achieve clinical remission. However, it remains unclear which biologics are effective in the patients with RA who have large joint involvement. Objectives: The aim of this study is to investigate the efficacy of anti-IL-6 receptor antibody (aIL-6) or TNF-inhibitor (TNFi) in the treatment of RA patients who have knee joint involvement. Methods: We enrolled the 784 patients who visited our hospitals in 2003 to 2019 and were treated with aIL-6 or TNFi more than 12 weeks. We divided the patients into 2 groups with or without knee joint involvement for further analysis. Knee joint involvement was defined as the patients had at least one swelling joint of knee at baseline. We investigated the CDAI levels at baseline and 12 weeks after the initiation of biologics. Results: Interestingly, the patients who had knee joint involvement with aIL-6 significantly ameliorated ΔCDAI (n=95, 15.0±10.8; mean±SD) compared to those with TNFi (n=148, 11.4±10.3) at 12 weeks (P=0.003). aIL-6 group consists of 95 tocilizumab treated patients. TNFi group includes 25 adalimumab, 25 certolizumab pegol, 14 etanercept, 54 golimumab and 30 infliximab treated patients. Baseline clinical characteristics of the 243 RA patients who had knee joint involvement were shown in Table 1 . Mean ages, sex and disease durations were not significantly different between the two groups. Baseline CDAI levels of aIL-6 group (24.8±11.8) were slightly elevated compared to those of TNFi group (21.7 ±10.9). Multivariate analysis adjusted for age, gender and baseline CDAI levels revealed that aIL-6 significantly improved ΔCDAI levels compared to TNFi (P=0.04). By contrast, in the RA patients who had no swelling of knee joints, there was no significant difference of ΔCDAI improvement between aIL-6 group (n=156, 5.5±7.4) and TNFi group (n=385, 6.7±8.9). Conclusion: Thus, these findings suggest that anti-IL-6 receptor antibody was more effective in the RA patients with knee joint involvement compared to TNF- inhibitor. References: [1]Burgers LE, et al.Ann Rheum Dis. 2018;77:e33. Disclosure of Interests: Yuichi Maeda Grant/research support from: YM received a research grant and/or speaker fee from Eli Lilly, Chugai, Pfizer, Bristol-Myers Squibb, and Mitsubishi-Tanabe, Speakers bureau: YM received a research grant and/or speaker fee from Eli Lilly, Chugai, Pfizer, Bristol-Myers Squibb, and Mitsubishi-Tanabe, Toru Hirano Grant/research support from: TH received a research grant and/or speaker fee from Astellas, Chugai, Nippon Shinyaku, Abbvie, Eisai, and Ono Pharmaceutical, Speakers bureau: TH received a research grant and/or speaker fee from Astellas, Chugai, Nippon Shinyaku, Abbvie, Eisai, and Ono Pharmaceutical, Ryota Hara Speakers bureau: RH received a speaker fee from AbbVie, Kosuke Ebina Grant/research support from: KE has received research grants from Abbie, Asahi-Kasei, Astellas, Chugai, Eisai, Ono Pharmaceutical, and UCB Japan., Employee of: KE is affiliated with the Department of Musculoskeletal Regenerative Medicine, Osaka University, Graduate School of Medicine, which is supported by Taisho., Speakers bureau: KE has received payments for lectures from Abbie, Asahi-Kasei, Astellas, Ayumi, Bristol-Myers Squibb, Chugai, Eisai, Eli Lilly, Janssen, Mitsubishi-Tanabe, Ono Pharmaceutical, Sanofi, and UCB Japan., Motomu Hashimoto Grant/research support from: Bristol-Myers Squibb, Eisai, and Eli Lilly and Company., Speakers bureau: Bristol-Myers Squibb and Mitsubishi Tanabe Pharma., Wataru Yamamoto: None declared, Kosaku Murakami Speakers bureau: AbbVie, Eisai, and Mitsubishi Tanabe Pharma., Takuya Kotani: None declared, Kenichiro Hata: None declared, Yonsu Son: None declared, Hideki Amuro: None declared, Akira Onishi Speakers bureau: AO received a speaker fee from Chugai, Ono Pharmaceutical, Eli Lilly, Mitsubishi-Tanabe, Asahi-Kasei, and Takeda, Jinno Sadao: None declared, Masaki Katayama: None declared, Atsushi Kumanogoh Grant/research support from: AK received a research grant and/or speaker fee from Mitsubishi-Tanabe, Chugai, Eisai, Asahi-Kasei, Astellas, Abbvie, Bristol-Myers Squibb, Ono Pharmaceutical, and Pfizer, Speakers bureau: AK received a research grant and/or speaker fee from Mitsubishi-Tanabe, Chugai, Eisai, Asahi-Kasei, Astellas, Abbvie, Bristol-Myers Squibb, Ono Pharmaceutical, and Pfizer